2016
DOI: 10.1111/all.12987
|View full text |Cite
|
Sign up to set email alerts
|

A dual CysLT1/2 antagonist attenuates allergen‐induced airway responses in subjects with mild allergic asthma

Abstract: Attenuation of EAR, LAR, and airway inflammation is consistent with cysLT blockade. Whether dual cysLT antagonism offers additional benefit for treatment of asthma requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…CysLTs released in response to allergen challenges in atopic subjects elicit bronchoconstriction primarily through CysLT 1 R (64). Although no studies have directly contrasted the effects of CysLT 1 R antagonists with those of 5-LO inhibition, a recent study demonstrated that a dual CysLT 1 R/CysLT 2 R antagonist, but not a CysLT 1 R-selective antagonist, prevented the increase in sputum eosinophils occurring in atopic asthmatic subjects following allergen inhalation, even though both drugs blocked the attendant changes in lung function (65). The markedly dysregulated cysLT synthesis, strong IL-33 expression, and high levels of tissue eosinophilia observed in AERD may reflect, in part, immunopathologic contributions from CysLT 2 R. The findings support the potential therapeutic utility of drugs with the capacity to block CysLT 2 R, alone or in combination with the other cysLT receptors, in AERD and other conditions characterized by robust type 2 immunopathology and cysLT production.…”
Section: Discussionmentioning
confidence: 99%
“…CysLTs released in response to allergen challenges in atopic subjects elicit bronchoconstriction primarily through CysLT 1 R (64). Although no studies have directly contrasted the effects of CysLT 1 R antagonists with those of 5-LO inhibition, a recent study demonstrated that a dual CysLT 1 R/CysLT 2 R antagonist, but not a CysLT 1 R-selective antagonist, prevented the increase in sputum eosinophils occurring in atopic asthmatic subjects following allergen inhalation, even though both drugs blocked the attendant changes in lung function (65). The markedly dysregulated cysLT synthesis, strong IL-33 expression, and high levels of tissue eosinophilia observed in AERD may reflect, in part, immunopathologic contributions from CysLT 2 R. The findings support the potential therapeutic utility of drugs with the capacity to block CysLT 2 R, alone or in combination with the other cysLT receptors, in AERD and other conditions characterized by robust type 2 immunopathology and cysLT production.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, angiotensin II receptor 1 (AT1R) has been shown to activate NOX1 likely via Gαq and PLCβ which activate PKC [29]. Evidence showed that thrombin can increase NOX1-dependent ROS generation by mechanisms involving PAR4 or EGFR transactivation [24,30,31]. Several studies have reported an upregulation of NOX4 in response to GPCR ligands such as angiotensin II (AT-II), urotensin-II, β-adrenergic agonists, renin and thrombin [32][33][34][35][36][37].…”
Section: Recently Described Roles Of G Protein Mutations In Tumorigenmentioning
confidence: 99%
“…With respect to testing of investigational therapies, allergen inhalation test was initially used to assess the first monoclonal antibody, omalizumab, directed at IgE, in the treatment of allergic asthma [61,62]. This study was followed by several others using inhaled allergen challenge as a proof of concept to evaluate small molecule inhibitors [63][64][65][66][67][68][69], novel corticosteroids, oligonucleotides and monoclonal antibodies [70][71][72][73][74][75][76][77].…”
Section: Assessment Of Potential New Asthma Therapiesmentioning
confidence: 99%